Use of herbal products for weight loss in Turkey - Bellikci-Koyu, Ezgi; Şarer-Yürekli, Banu Pınar; Seckiner, Selda; Özdemir, Nilüfer; Buyuktuncer, Zehra (Progress in Nutrition, 2020)
Obesity treatment is a long-term challenge that requires a constant change in lifestyle and behaviors. Therefore, patients are usually interested in methods promising rapid weight loss. In this study, we aimed to determine the frequency of herbal product use by overweight and obese individuals for weight management. A cross-sectional study was conducted on 464 individuals admitted to an endocrinology clinic in a hospital in Turkey. Socio-demographic status, medical history, and information about herbal product usage were recorded by researchers using a data collection form. The percentage of participants using herbal products for weight loss, was determined as 24.1% (n:112). Herbal product users were younger and had higher body mass index compared to non-users (p<0.01, for each). Gender and marital status were also related to herbal product use, and it was higher in women and singles (p<0.05, for each). The most preferred products were mixed herbal teas (50.9%), green tea, parsley, and cinnamon. Herbalists (56.3%) and local markets (24.1%) were the most popular places to buy herbal products. A large proportion of patients (88.4%) did not inform health professionals about their herbal usage. Using herbal products for weight management is common among overweight and obese individuals in Turkey. Therefore, it may be suggested that health professionals should monitor the use of these products and patient-physician communication about herbal medicine should be strengthened.